Valuing Human Resources to Create Value - A Case Study of Infosys Ltd - Mehta, Pooja (Prabandhan: Indian Journal of Management, 2011)
The significance of employees in service industries has been recognized worldwide by senior executives for many decades, and they are aware that the services provided by human resources are the key to competitive advantage in the market place. Human Resource Accounting (HRA) as an information system tells management about the identification, recording, and reporting of the investment in and returns from the employment of its human resources. As the organizations are spending a huge amount on training&retaining the employees, so, it is essential to have an overview about how the human resources are valued in an organization. The present paper provides an outstanding foundation to conceptualize and frame the idea for the valuation of human resources in the working arena. For this purpose, a case study of Infosys Ltd. is taken into consideration for evaluating its Human Resource Valuation practices. The study indicates the technique this company is following for the valuation purpose and analyses how this valuation is enhancing the company's functioning. The findings of the study indicate that human-resource valuation at Infosys Ltd. is worthwhile, as evident from its comparatively satisfactory attrition rate and a large number of awards it achieved in the capacity of one of the best employers.